(3GdehVM dePGgH GdbQGA hGNJdGage aj GdaJM hGdEeGdIs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s
(3ChdgG (B:s
(3hHYO aEf Chd eG JUQa ajg Gdgee cGf CfaY eG Cda aj Pdc GdCQLhRI GdeSeGg HGdebOeI s
(3BNQgG (B:s
(3hTQM hLhgg hJdNjU eYGfjg Ydi MSH eG GTJQWfGg s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B292 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B188s
Keywords: (3GdbQGAGJ hGdJLhjOs